EMOTION AND ITS RELEVANCE TO THE LANGUAGE AND LINGUISTICS - Hayitboeva Оltinoy Shonazar qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article focuses on the relevance of emotion for language and linguistics. Emotions play an important role in the way we perceive, process, interpret, and use language. It examines how emotion influences language use and language learning, as well as how language affects our emotions. The findings suggest emotion is an integral part of language and should be considered in language models.